Principles of Diabetes Mellitus - Poretsky, Leonid (Springer International Publishing : Imprint: Springer, 2017)
The third edition of this important work is a timely update to the comprehensive textbook first published in 2002 and reissued in a second edition in 2010. The past few years have witnessed major developments in our understanding of diabetes and in therapeutic approaches to this disease and its numerous complications. Thus, all chapters have been significantly revised and updated with current evidence and best practices, and four brand new chapters are included, discussing the potential role of vitamin D in the pathogenesis of diabetes, peculiarities of diabetes in the elderly, oral manifestations of diabetes, and the current state of bariatric surgery. Written by an international group of experts and carefully edited by a leading authority on the subject, Principles of Diabetes Mellitus, Third Edition is an invaluable resource for researchers and physicians of all specialties, as well as medical students and investigators of all aspects of diabetes, who deal with an illness that has reached epidemic proportions.- Resumé vydavatel